If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 662 = 249(2 + s) 662 = (2 * 249 + s * 249) 662 = (498 + 249s) Solving 662 = 498 + 249s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-249s' to each side of the equation. 662 + -249s = 498 + 249s + -249s Combine like terms: 249s + -249s = 0 662 + -249s = 498 + 0 662 + -249s = 498 Add '-662' to each side of the equation. 662 + -662 + -249s = 498 + -662 Combine like terms: 662 + -662 = 0 0 + -249s = 498 + -662 -249s = 498 + -662 Combine like terms: 498 + -662 = -164 -249s = -164 Divide each side by '-249'. s = 0.6586345382 Simplifying s = 0.6586345382
| F+(1.7*F)=27 | | 29(P-34)=464 | | 8(x+1)-2(x-3)=2(x-2)+3(x-2) | | 9x=2.5x+60 | | 6t-c=10 | | 5x-7x+46=4x+28 | | 4-5x=20z | | P-0.20p=632 | | (7x-2)(x+1)=0 | | -9.1=0.9-5y | | 2.18n=2n+2 | | 8-4(p+2)=2p-8(p+4) | | 16a+2a^4=1 | | 37=8x-11 | | 5r-3s=24 | | X+4.5=8.2 | | f(x)=(x+5)(x-3) | | 29=29+0.08x | | 2b-w=m | | n^2+100-39=0 | | 2X+2-4X=4-2X-2 | | 7x+4=-5+4x+15 | | -2=0.125x+3 | | 8-2(2r-3)=0 | | x+y^2-x-y^2= | | -97+12= | | -2x(x-8)-28=-12 | | 100+11= | | (x+1)*2=3x*2 | | (x+1)*2=3*2 | | X^3-3x^2-80x-28=0 | | -2(x-4)=4x |